Short-term high-fat diet feeding plus acute ethanol binge induced acute liver injury in mice via oxidative stress, inflammation and pyroptosis - Deng, Yao; Chen, Xinling; Guo, Wenhai; Chen, Yun; Xu, Luyao; Suo, Wenting; Liu, Wei; Dai, Jiaying; Wang, Kangrong; Li, Qiuling; Lu, Chengqin; Dai, Min; et al. (Frontiers in Pharmacology, 2025)
BackgroundEthanol binge and obesity are the key risk factors for alcohol-related liver disease (ALD) and nonalcoholic fatty liver disease (NAFLD), respectively. The human beings have a habit of drinking alcohol and consuming high calorie foods, these two factors often coexist, and thus contributing to the liver injury. However, the mechanisms of a short-term consumption of high-fat diet (HFD) plus alcohol binge-induced acute liver injury are unclear.MethodsMale C57BL/6 mice (aged 8–10 weeks) were fed a HFD or HFD Control diet for 3 days. Then, they received a single dose of ethanol or the same volume of distilled water by oral gavage. The liver damage was evaluated after 9 h of ethanol gavage.ResultsShort-term (3 days) HFD feeding plus ethanol binge significantly aggravated liver injury and steatosis in mice as indicated by the increased serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), and triglyceride (TG) levels, the upregulated hepatic TG levels, and Oil Red O staining and H&E staining. Mechanistically, short-term HFD feeding plus ethanol binge disturbed hepatic redox homeostasis by increasing 3-nitrotyrosine (3-NT), malondialdehyde (MDA) and myeloperoxidase (MPO) levels, while decreasing glutathione (GSH) levels. HFD and alcohol co-consumption also increased hepatic TNF-α, IL-1β and IL-18 via enhancing the phosphorylation of MAPK (ERK1/2, p38 and JNK) and NF-κB. The canonical (Caspase-1 to GSDMD) and non-canonical pyroptosis signaling (Caspase-8/11 to GSDMD, and Caspase-3 to GSDME) further contributed to the acute liver injury.ConclusionShort-term HFD feeding plus a single dose of ethanol gavage can significantly exacerbate acute liver injury and hepatic fat deposition in mice by enhancing oxidative stress, MAPK and NF-κB signaling, and Caspase-1/8/11-GSDMD and Caspase-3-GSDME pyroptosis signaling.